CAPTIVE PORTALDAN IMPLEMENTASI BANDWIDTH MANAGEMENT DI STIKES St. ELISABETH SEMARANG - Eko Siswanto; Indra Ava Dianta; Danang Danang (MANAJEMEN, 2021)
Computer network is one of the important technologies in the field of information and communication technology which is currently growing rapidly and rapidly. Computer networks within a company or agency are very helpful for work activities to be carried out quickly, precisely and efficiently. Basically, computer network technology cannot be separated by cable as an intermediary medium. Excessive use of cable media will certainly affect the mobility and flexibility of internet and intranet users. Wireless technology is a solution to meet the need for high mobility and flexibility. Wireless technology uses radio waves as a transmission medium, this technology has several advantages including high freedom and flexibility. Users or users can access the internet or intranet as long as they are within wireless range.STICK St. Elisabeth as one of the educational institutions in the health sector so far has had a wireless network or hotspot area, so that teaching staff, students, and visitors at STIKES St. Elisabeth who wants to be connected to the internet or intranet can directly connect to the network without going through network security. This causes the user hotspot not to be managed so that it affects the efficiency of bandwidth usage and network security. To provide a solution to these problems, the authors propose the design of Captive Portal and Implementation of Bandwidth Management STIKES St. Elisabeth uses a Mikrotik RB750G Router.This final project report will describe the stages of designing and implementing hotspot network security at STIKES St. Elisabeth. These stages include analysis of existing networks, planning and design stages of network security which consist of determining security systems, determining topology, data collection and user management. The implementation phase is the process of installing and configuring the network security device system. The things that have been done, and the testing of the security system will be reviewed at the end of the report.